Implementasi Strategi Guru dalam Mengembangkan Keterampilan Motorik Kasar pada Anak di TK IT Bunayya 7 Al-Hijrah Kecamatan Percut Sei Tuan - Intan Syahdila Hasibuan; Arlina Arlina; Enny Nazrah Pulungan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to determine and describe the teacher's strategy in developing gross motor skills in children at Bunayya 7 Al-Hijrah IT Kindergarten. The research methodology uses phenomenological qualitative, with data collected through observation, interviews, and documentation. The data analysis used data reduction, data presentation, and conclusion drawing. The results showed that: 1) The strategy of activities carried out by teachers to develop gross motor skills at Bunayya 7 Al Hijrah IT Kindergarten, Percut Sei Tuan District, includes doing gymnastics, playing games, practicing prayers, doing role-playing activities, singing asmaul husna with movements, warming up through ice breaking, getting children used to ablution, and getting children used to using the toilet (toilet training). 2) From these activities, the teacher has several strategies in developing gross motor skills, including the preparation of media and teaching materials by the teacher to be applied in learning, the teacher teaches warm-up movements as an introduction to the activity, the teacher gives explanations and direct examples to children, the teacher provides assistance to children, the teacher gives praise and motivation, the teacher repeats so that children are able to master and get used to doing movements, and the teacher evaluates children. 3) Teachers choose to use this strategy because it is effective for developing gross motor skills such as agility, strength, balance, and coordination in a fun way for children.